Milling of al 6060 alloy with DLC coated cutting tools - AY, MUSTAFA (My University, 2019)
In this study, the effects of rotation, feed rate, and MQL cooling system flow on surface roughness and cutting forces in milling Al 6060 alloy with DLC coated cutting tools are investigated. Taguchi method was used in the test design. Thus, time and cost are saved in the tests. The results obtained from the tests were optimized and improved. Surface roughness and performance were improved with the Taguchi method. In this study, optimal workability of Al 6060 material with DLC coated end mill was tried to be determined with grey relational analysis and surface roughness and cutting force optimization was made. Ideal values were obtained when the revolution was 3500 rpm; the feed rate was 450 mm/min. Moreover, the MQL rate was 30 l/h.
Keywords: A1 6060; Cutting; GRA; MQL; Taguchi